Pharmacogenetic associations of CYP2D6 and CYP2C19 variants with anticholinergic drug burden and hyposalivation - Korczeniewska, Olga A.; Diehl, Scott; Barmak, Abdul Basir; Wu, Tong Tong; Eliav, Eli; Arany, Szilvia (Frontiers in Pharmacology, 2025)
IntroductionAnticholinergic medications frequently cause hyposalivation (decreased saliva flow) through parasympathetic inhibition. This adverse effect is related to anticholinergic burden, reflecting the cumulative exposure to drugs with anticholinergic properties. Genetic variation in CYP genes, which encode drug-metabolizing enzymes, alters drug metabolism, potentially influencing systemic anticholinergic burden. This study investigated whether polymorphisms in the CYP2D6 and CYP2C19 genes are associated with anticholinergic burden and hyposalivation.MethodsAdults taking at least one CYP substrate anticholinergic medication reporting xerostomia (oral dryness) were recruited. Anticholinergic burden was quantified using the Anticholinergic Drug Scale (ADS) and Serum Anticholinergic Activity (SAA). Salivary assessment included unstimulated whole saliva (UWS) and minor saliva flow (MSF). Participants were genotyped for functional variants of CYP2D6 and CYP2C19.ResultsCYP2D6 rs28371725 polymorphism was associated with low MSF and increased SAA in severe hyposalivation (genotype relative risk: 12.75, 95% CI 1.45–112.12). Additionally, variants (rs28371706, rs5030655) were associated with high ADS scores. Individuals with reduced CYP2D6 activity presented with higher systemic exposure and a greater anticholinergic burden for a given dose, as reflected by higher ADS and SAA. CYP2C19 polymorphisms showed no strong associations with salivary outcomes or anticholinergic burden.ConclusionGenetic variation in CYP2D6 contributes to interindividual differences in systemic anticholinergic burden and hyposalivation. Pharmacogenetic profiling of CYP450 genes may help identify patients at risk of xerostomia from anticholinergic therapy, supporting more personalized and optimized anticholinergic prescribing.